ANÁLISE DOS FATORES DETERMINANTES PARA O ABANDONO DE ADOLESCENTES NO FUTSAL - Cassiá Antônio Melo Reis (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Currently futsal is one of the most practiced sports for teens, however, many of these young people drop out this form. The objective of this study was evaluated determinants factors of dropout from adolescents in futsal. We interviewed 20 adolescents aged between 13 and 15 years and who attend the selection criteria. The instrument used was a questionnaire consisting of 20 closed questions with alternate choice of factors related to the abandonment of sports. Based on the analysis of data obtained from questionnaires results: showed that the main reasons given for adolescents to abandon classes futsal in their respective schools were the monotony of training with 55%, because my colleagues dropped to 40%, lack of support 30% of the technical, low participation in training and not as good as I and a few competitions and presentations with 25%. Comparing this with other studies in the literature, it is observed that there are some similarities in the results, especially as regards the influence of coach / teacher as a determinant for abandonment of adolescents in schools for futsal. We conclude that the factors related to the approaches adopted by teachers and coaches should be rethought, because these misconceptions not only methodological but also an organizational and human are determinants of dropout from adolescents in futsal.